2013
DOI: 10.1371/journal.pone.0077743
|View full text |Cite
|
Sign up to set email alerts
|

Haematinic Deficiency and Macrocytosis in Middle-Aged and Older Adults

Abstract: ObjectiveTo assess the prevalence and determinants of haematinic deficiency (lack of B12 folate or iron) and macrocytosis in blood from a national population-based study of middle-aged and older adults.MethodsA cross-sectional study involving 1,207 adults aged ≥45 years, recruited from a sub-study of the Irish National Survey of Lifestyle Attitudes and Nutrition (SLÁN 2007). Participants completed a health and lifestyle questionnaire and a standard food frequency questionnaire. Non-fasting blood samples were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
15
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 25 publications
3
15
3
Order By: Relevance
“…It is notable that the anemias within this group were of mild severity, with an average Hb level of 10.9 g/dL for females and 12.1 g/dL for males (Table 3). The increased MCV and MCH values observed in this study are consistent with those in previous reports [29,32]. In contrast, a decreasing trend of circulating RBCs may reflect a lower rate of erythropoiesis in older age groups.…”
Section: Discussionsupporting
confidence: 92%
“…It is notable that the anemias within this group were of mild severity, with an average Hb level of 10.9 g/dL for females and 12.1 g/dL for males (Table 3). The increased MCV and MCH values observed in this study are consistent with those in previous reports [29,32]. In contrast, a decreasing trend of circulating RBCs may reflect a lower rate of erythropoiesis in older age groups.…”
Section: Discussionsupporting
confidence: 92%
“…The commonest causes of iron deficiency in the general population are inadequate intake, poor absorption of iron and, in particular, menstruation [1,2,3,4,5]. This helps explain the increased daily iron requirement and higher deficiency rates in women versus men [5,6,7,8]. Supplementation with oral iron is well established to prevent and treat iron deficiency anaemia and symptomatic fatigue [5].…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation with oral iron is well established to prevent and treat iron deficiency anaemia and symptomatic fatigue [5]. However, iron food fortification and oral iron supplements are frequently limited by poor absorption and poor tolerability [3,4,7,8]. …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this association was independent of known causes of macrocytosis, including alcohol use. A few years ago, McNamee et al 5 and O'Reilly et al 6 reinvestigated the association between smoking as unrecognized cause of macrocytosis and showed that cigarette smoking was a significant risk factor for macrocytosis, independent of other known causes. Unfortunately, at present cigarette smoking is still not mentioned in textbooks and major guidelines, and clinicians are generally unaware of this association.…”
mentioning
confidence: 99%
“…Several studies on the use of venetoclax as single agent in relapsed/ refractory AML (r/r AML) demonstrated clinical activity with tolerable and safe profile 3 ; furthermore the addition of venetoclax to decitabine or azacitidine seems to sensitize AML cells to these hypomethylating agents (HMAs), in particular for patients with IDH mutations. [4][5][6] Relapsed AML after allogeneic hematopoietic stem cell transplantation (HSCT) have poor prognosis despite numerous therapies…”
mentioning
confidence: 99%